Effects of Job Embeddedness, OCB, and Satisfaction on Turnover Intention - Renaldo Evipania; Albert Surya Wanasida (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study aims to analyze the influence of Job Embeddedness (JE) and Organizational Citizenship Behavior (OCB) on Turnover Intention (TI), with Job Satisfaction (JS) as a mediating variable. Data were collected using questionnaires through the judgmental sampling method. The sample size was determined using G*Power software, which calculated a minimum of 77 respondents; however, this study used 119 respondents to enhance the reliability of the results. The data were analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The results show that Job Embeddedness has a significant negative effect on Turnover Intention and a significant positive effect on OCB and Job Satisfaction. OCB has a significant positive effect on Job Satisfaction but does not significantly affect Turnover Intention. Job Satisfaction has a significant negative effect on Turnover Intention and acts as a mediating variable in the relationship between Job Embeddedness and Turnover Intention, as well as between OCB and Turnover Intention.This research contributes to providing insights for organizations to reduce employees' intention to leave by strengthening Job Embeddedness, increasing OCB, and enhancing Job Satisfaction, thereby creating a conducive work environment to retain employees.